Evaluation of the cytotoxic effects of the colchicine compound isolated from the leaves of Calotropis procera (Ait) against MCF-7 and SK-GT-4 cancer cell lines. (Baghdad Science Journal, 2023)
Alkaloids are regarded as important nitrogen-containing chemical compounds that serve as a rich source for discovering and developing new drugs where most plant-origin alkaloids have antiproliferation effects on different kinds of cancers. Alkaloids’ continence of Calotropis procera leaves are detected by two biochemical alkaloid reagents. Also GC-MS analysis for leaf alkaloid extract was done that showed the existence of one type of alkaloid compound at retention time12.8min detected as colchicine (C22H25N06( by comparing it with colchicine standard reference (Sigma Aldrich) with M.wt 399g/mol and percentage area 7.1%. Furthermore, identification, separation, and purification for purified colchicine compound were conducted by HPLC technique that gave one main peak at RT reached 2.5min compared with the standard reference. Evaluation of the anticancer activity of purified colchicine on two (MCF-7 &SK-GT-4) cell lines revealed significant cytotoxicity on the MCF-7 cell line that was superior to its cytotoxicity on the SK-GT4 cell line. With calculated IC50 reached 55.33µg/ml &522 µg/ml respectively.